Interim thymus and activation regulated chemokine versus interim 18F‐fluorodeoxyglucose positron‐emission tomography in classical Hodgkin lymphoma response evaluation. (27th February 2020) - Plattel, Wouter J.; Visser, Lydia; Diepstra, Arjan; Glaudemans, Andor W. J. M.; Nijland, Marcel; van Meerten, Tom; Kluin‐Nelemans, Hanneke C.; van Imhoff, Gustaaf W.; van den Berg, Anke
Summary: Serum thymus and activation regulated chemokine (TARC) levels reflect classical Hodgkin lymphoma (cHL) disease activity and correspond with treatment response. We compared mid‐treatment interim TARC (iTARC) with interim 18 F‐fluorodeoxyglucose positron‐emission tomography (iPET) imaging to predict modified progression‐free survival (mPFS) in a group of 95 patients with cHL. High iTARC levels were found in nine and positive iPET in 17 patients. The positive predictive value (PPV) of iTARC for a 5‐year mPFS event was 88% compared to 47% for iPET. The negative predictive value was comparable at 86% for iTARC and 85% for iPET. Serum iTARC levels more accurately reflect treatment response with a higher PPV compared to iPET.